2022
DOI: 10.1093/cid/ciac127
|View full text |Cite
|
Sign up to set email alerts
|

AmBisome Monotherapy and Combination AmBisome–Miltefosine Therapy for the Treatment of Visceral Leishmaniasis in Patients Coinfected With Human Immunodeficiency Virus in India: A Randomized Open-Label, Parallel-Arm, Phase 3 Trial

Abstract: Background Visceral leishmaniasis (VL) in patients living with Human-Immunodeficiency-Virus (HIV) presents an increasingly important patient cohort in areas where both infections are endemic. Evidence for treatment is sparce, with no high-quality studies from the Indian sub-continent. Methods This is a randomised open label, parallel arm phase-3 trial conducted within a single hospital in Patna, India. 150 patients aged ≥18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
(18 reference statements)
0
8
1
Order By: Relevance
“…The overall end-of-treatment cure rate among the VL–HIV coinfected group who started AmBisome and miltefosine combination therapy was 54.5% (12/22). Our finding is lower than previous reports in northwest Ethiopia [ 35 , 36 ] and India [ 37 ], where cure rates of AmBisome and miltefosine combination therapy among HIV coinfected cases were reported to be 67–83.8% and 96%, respectively. The lower end-of-treatment cure rate of AmBisome and miltefosine combination therapy in our case might partly be attributed to the long duration of illness at the time of diagnosis among HIV coinfected cases.…”
Section: Discussioncontrasting
confidence: 92%
“…The overall end-of-treatment cure rate among the VL–HIV coinfected group who started AmBisome and miltefosine combination therapy was 54.5% (12/22). Our finding is lower than previous reports in northwest Ethiopia [ 35 , 36 ] and India [ 37 ], where cure rates of AmBisome and miltefosine combination therapy among HIV coinfected cases were reported to be 67–83.8% and 96%, respectively. The lower end-of-treatment cure rate of AmBisome and miltefosine combination therapy in our case might partly be attributed to the long duration of illness at the time of diagnosis among HIV coinfected cases.…”
Section: Discussioncontrasting
confidence: 92%
“…Finally, none of the studies identified enrolled patients with HIV or other comorbidities. Although these comorbidities are commonly reported in visceral leishmaniasis [29, 30], these conditions have been less pronounced with PKDL, and only sporadic cases have been reported across India, Africa, Europe, and South America [31-33]. Overall, these observations regarding the patient spectrum show substantial knowledge gaps in treatment efficacy in these specific subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…At the treatment centre in Ethiopia where the clinical trial was conducted [ 7 ], physicians attempted to contact all the patients who had participated in the trial, while ensuring voluntary participation, confidentiality, and anonymity. A similar process was followed in India [ 8 ], except that a random sample of patients was contacted. Wherever possible, attempts were made to contact all VL patients under trial by the treating physicians.…”
Section: Methodsmentioning
confidence: 99%
“…This is a major challenge considering that L. infantum has different drug susceptibilities and less virulence than L. donovani and that relapses due to L. donovani occur at a lower CD4+ count. While currently the World Health Organization (WHO) recommends monotherapy of liposomal amphotericin B infusion at a dose of 3-5 mg/kg daily or intermittently for 10 doses (days 1-5, 10, 17, 24, 31 and 38) up to a total dose of 40 mg/kg as the firstline treatment [1], new evidence on combination regimens has become available from clinical trials recruiting HIV-VL coinfected patients in East Africa [7] and South-East Asia [8]. The regimens consist of combination of liposomal amphotericin B infusion (at a dose of 5 mg/kg on days 1, 3, 5, 7, 9 and 11, up to a total dose of 30 mg/kg body weight) and oral miltefosine (100 mg in divided doses for 14 days in South-East Asia and 28 days in East Africa respectively).…”
Section: Introductionmentioning
confidence: 99%